Combining Mg-Zn-Ca Bulk Metallic Glass with a Mesoporous Silica Nanocomposite for Bone Tissue Engineering - Yun Shin Chu; Pei-Chun Wong; Jason Shian-Ching Jang; Chih-Hwa Chen; Si-Han Wu (MDPI AG, 2022)
Mg-Zn-Ca bulk metallic glass (BMG) is a promising orthopedic fixation implant because of its biodegradable and biocompatible properties. Structural supporting bone implants with osteoinduction properties for effective bone regeneration have been highly desired in recent years. Osteogenic growth peptide (OGP) can increase the proliferation and differentiation of mesenchymal stem cells and enhance the mineralization of osteoblast cells. However, the short half-life and non-specificity to target areas limit applications of OGP. Mesoporous silica nanoparticles (MSNs) as nanocarriers possess excellent properties, such as easy surface modification, superior targeting efficiency, and high loading capacity of drugs or proteins. Accordingly, we propose a system of combining the OGP-containing MSNs with Mg-Zn-Ca BMG materials to promote bone regeneration. In this work, we conjugated cysteine-containing OGP (cgOGP, 16 a.a.) to interior walls of channels in MSNs and maintained the dispersity of MSNs via PEGylation. An in vitro study showed that metal ions released from Mg-Zn-Ca BMG promoted cell proliferation and migration and elevated alkaline phosphatase (ALP) activity and mineralization. On treating cells with both BMG ion-containing Minimum Essential Medium Eagle-alpha modification (α-MEM) and OGP-conjugated MSNs, enhanced focal adhesion turnover and promoted differentiation were observed. Hematological analyses showed the biocompatible nature of this BMG/nanocomposite system. In addition, in vivo micro-computed tomographic and histological observations revealed that our system stimulated osteogenesis and new bone formation around the implant site.